Carbon disclosure, emission intensity and cost of equity capital: multi‐country evidence. (5th June 2019) - Bui, Binh; Moses, Olayinka; Houqe, Muhammad N.
Abstract: This study examines the joint effect of carbon disclosure and greenhouse gas (GHG) emissions on firms' implied cost of equity capital (COC). Based on 4655 firm‐year observations across 34 countries, we find firms' GHG emission intensity to be positively associated with COC. However, we find also that the penalty linked with higher COC is moderated by extensive carbon disclosure. We provide evidence that the extent of carbon disclosure helps reduce the premium required by investors to compensate for poor carbon performance. Our study provides insights to policymakers, investors and managers on the combined effect of carbon disclosure, and emission intensity.